The effect of early multimodal rehabilitation in abdominal hysterectomy on postoperative period - Lashkul, Olga (ScienceRise: Medical Science, 2017)
The aim of research was to estimate the influence of the use of early multimodal rehabilitation concept on postoperative period after scheduled abdominal hysterectomy. Methods. 41 female patients, divided in two groups, were involved in the study. In the main group (19 patients) early multimodal rehabilitation protocol was used. Preoperative period: informing and teaching the patient; bowel preparation rejection; starvation rejection; the use of dietary carbohydrate mixes; thromboembolic complications prevention. Intraoperative period: antibiotic prophylaxis; regional (epidural analgesia); short acting anesthetics; postoperative infusion therapy limitation; rejection of nasogastric intubation; normothermia; the routine use of drains rejection. Postoperative period: effective pain relief; non opioid analgesics; nausea and vomiting prevention; early mobilization (after epidural block regression); early enteral nutrition. In the control group, hysterectomy via laparotomy was performed using combined anesthesia (Sevoflurane + epidural analgesia + Fentanyl) with artificial lung ventilation. In the control group, general anesthesia was implemented using Sevoflurane, system analgesia – using Fentanyl (5 μg/kg/hour). In the main group, anesthesia was implemented using Fentanyl (3–5 μg / kg/ hour) and epidural 0.5 % solution of Bupivacaine (6–8 ml). During postoperative period, in the main group prolonged epidural analgesia by small boluses of 0.25 % Bupivacaine solution (4 ml/hour) in combination with system administration of Dexketoprofen (100–150 mg/day) + Ketorolac (60 mg/day) + Paracetamol (2000 mg / day) was used. In the control group, postoperative analgesia included Paracetamol 3000 mg / day, Dexketoprofen 150–200 mg/day, Tramadol 50–100 mg/day. Besides, pain level (VAS) within 12 and 24 hours after operation at rest and during coughing was estimated. Results. The groups were identical by anamnestic (start of menstruation, number of pregnancies, births, abortions and pregnancy losses), anthropometric and demographic characteristics, as well as by duration of the surgeries, blood loss volume and preoperative parameters of mean arterial pressure and heart rate. Pain level when coughing in the control group was higher than the one in the main group, statistical difference was determined in 12 and 24 hours, and it was higher than30 mm, which required more analgesics. An adequate postoperative analgesia allows starting early activation of the patients in the control group. Postoperative bed-day in patients of the main group (FTS) was considerably shorter than in patients of the control group without FTS. Conclusion. The proposed complex of measures is one of the ways for the fast track gynecological surgery operations concept implementation. This approach allows early discharge, which undoubtedly has direct economic effect and increases prestige of doctor and medical institution